1996
DOI: 10.1083/jcb.134.3.699
|View full text |Cite
|
Sign up to set email alerts
|

emo-1, a Caenorhabditis elegans Sec61p gamma homologue, is required for oocyte development and ovulation.

Abstract: Abstract. emo-l(ozl) is a member of a class of hermaphrodite sterile mutations in Caenorhabditis elegans that produce endomitotic oocytes in the gonad arm. Oocytes in emo-1 (ozl) mutants exhibit multiple defects during oogenesis. After meiotic maturation, ovulation fails, trapping oocytes in the gonad arm where they become endomitotic, erno-1 encodes a homologue of the Sec61p ~/subunit, a protein necessary for translocation of secretory and transmembrane proteins into the endoplasmic reticulum of yeast and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
136
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 61 publications
11
136
0
Order By: Relevance
“…However, in both CeTMI,II (RNAi) and CeTMI, II,III,IV (RNAi) worms, oocytes at the proximal gonads had a large accumulation of DNA ( Figure 1d, arrowhead), indicating that there was endomitotic replication of DNA in the oocytes, which became highly polyploid. This phenotype resembles the previously described endomitotic oocytes in gonadal arms phenotype (Emo) that is observed when ovulation is defective (Iwasaki et al, 1996). The Emo phenotype of CeTM (RNAi) worms was very severe, such that oocytes or embryos were not observed in the spermatheca or uterus ( Figure 1b and Table 1), suggesting that there was no ovulation.…”
Section: Tropomyosin Is Essential For Ovulationsupporting
confidence: 48%
See 1 more Smart Citation
“…However, in both CeTMI,II (RNAi) and CeTMI, II,III,IV (RNAi) worms, oocytes at the proximal gonads had a large accumulation of DNA ( Figure 1d, arrowhead), indicating that there was endomitotic replication of DNA in the oocytes, which became highly polyploid. This phenotype resembles the previously described endomitotic oocytes in gonadal arms phenotype (Emo) that is observed when ovulation is defective (Iwasaki et al, 1996). The Emo phenotype of CeTM (RNAi) worms was very severe, such that oocytes or embryos were not observed in the spermatheca or uterus ( Figure 1b and Table 1), suggesting that there was no ovulation.…”
Section: Tropomyosin Is Essential For Ovulationsupporting
confidence: 48%
“…Thus, when the cleavage was complete, the nucleus was restricted to only one of the two daughter cells, leaving the other cell anuclear (Figure 2j, asterisk; Video 2). In the absence of ovulation, maturation of the second or third proximal oocyte was often observed (our unpublished data), indicating that a signal to induce oocyte maturation can reach distally located oocytes as demonstrated previously (Iwasaki et al, 1996). Therefore, suppression of TM specifically caused a defect in the contractile activity of the ovary, but not in the process of oocyte maturation.…”
Section: Tropomyosin and Troponin In Ovulationmentioning
confidence: 80%
“…When ovulation fails, a mature oocyte remains in the proximal ovary, repeats DNA synthesis without cell division, and becomes endomitotic (Iwasaki et al, 1996;McCarter et al, 1997McCarter et al, , 1999. This phenotype is designated as Emo (endomytotic oocytes in the proximal ovary) and is characterized by intense staining by 4Ј6-diamidino-2-phenylindole, dihydrochloride (DAPI) of overly amplified nuclear DNA in endomitotic oocytes ( Fig.…”
Section: Roles Of the Myofibrillar Components In Ovulationmentioning
confidence: 99%
“…This phenotype is designated as Emo (endomytotic oocytes in the proximal ovary) and is characterized by intense staining by 4Ј6-diamidino-2-phenylindole, dihydrochloride (DAPI) of overly amplified nuclear DNA in endomitotic oocytes ( Fig. 7C, arrows; Iwasaki et al, 1996). The ovulation process is also regulated by signals from sperm and oocytes.…”
Section: Roles Of the Myofibrillar Components In Ovulationmentioning
confidence: 99%
“…org/supplemental/). Time-lapse analysis has shown that the Emo phenotype results when the oocyte undergoes maturation but ovulation fails, with the resulting unfertilized oocyte remaining in the gonad and undergoing endoreduplication cycles (Iwasaki et al 1996;McCarter et al 1997;Rose et al 1997). The Emo phenotype observed with partial mpk-1 lf suggests that maturation occurred normally but ovulation failed; however, until these intermittent/low-frequency events Germline MPK-1 Function and Activation 2051 are examined by time-lapse microscopy, this interpretation is uncertain.…”
mentioning
confidence: 95%